Comparison of Election Law in Indonesia, England, The United States, and Malaysia - Dina Cynthia Putri Dina Cynthia Putri; Handar Subhandi Bakhtiar (Journal of Ius Comparatum Law Studies, 2026)
A General election is a forum or medium for the people to express their sovereignty. Ideally, the general election aims to regularly and peacefully effect changes in government power in accordance with the mechanism guaranteed and determined by the constitution. This study aims to examine how differences in the General Election Systems of Indonesia, the United Kingdom, and the United States affect aspects of government systems, election frequencies, political participation, and party systems. Second, identify the strengths and weaknesses of the election process in Indonesia, Britain, and the United States. Based on the study's results, the electoral system in Indonesia follows the principle of direct representative democracy.In contrast, in the UK, the general election adopts the parliamentary system with the first-past-the-post principle. In the United States, the electoral system combines representative democracy and Electoral College principles to elect the president, while in Malaysia, it uses the FPTP system. In addition, there are advantages and disadvantages to elections in these three countries: for example, in Indonesia, elections directly confer strong legitimacy and increase people's political participation, but they are vulnerable to money politics. These four countries use different approaches to their democratic systems, even though their goals remain aligned: to provide people with opportunities to vote for their leaders and representatives.